Prion protein and aging - Gasperini, Lisa; Legname, Giuseppe (Frontiers in Cell and Developmental Biology, 2014)
The cellular prion protein (PrPC) has been widely investigated ever since its conformational isoform, the prion (or PrPSc), was identified as the etiological agent of prion disorders. The high homology shared by the PrPC-encoding gene among mammals, its high turnover rate and expression in every tissue strongly suggest that PrPC may possess key physiological functions. Therefore, defining PrPC roles, properties and fate in the physiology of mammalian cells would be fundamental to understand its pathological involvement in prion diseases. Since the incidence of these neurodegenerative disorders is enhanced in aging, understanding PrPC functions in this life phase may be of crucial importance. Indeed, a large body of evidence suggests that PrPC plays a neuroprotective and antioxidant role. Moreover, it has been suggested that PrPC is involved in Alzheimer disease, another neurodegenerative pathology that develops predominantly in the aging population. In prion diseases, PrPC function is likely lost upon protein aggregation occurring in the course of the disease. Additionally, the aging process may alter PrPC biochemical properties, thus influencing its propensity to convert into PrPSc. Both phenomena may contribute to the disease development and progression. In Alzheimer disease, PrPC has a controversial role because its presence seems to mediate β-amyloid toxicity, while its down-regulation correlates with neuronal death. The role of PrPC in aging has been investigated from different perspectives, often leading to contrasting results. The putative protein functions in aging have been studied in relation to memory, behavior and myelin maintenance. In aging mice, PrPC changes in subcellular localization and post-translational modifications have been explored in an attempt to relate them to different protein roles and propensity to convert into PrPSc. Here we provide an overview of the most relevant studies attempting to delineate PrPC functions and fate in aging.